2020
DOI: 10.1186/s13104-020-05016-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gum Arabic (Acacia senegal) on C-reactive protein level among sickle cell anemia patients

Abstract: Objectives: Inflammation is ongoing process among sickle cell anemia even during steady state. C reactive protein (CRP) is cardinal marker that utilized widely as inflammatory indicator. Gum Arabic (GA) is gummy exudates from Acacia senegal tree. Fermentation by colonic bacteria increases serum butyrate concentrations, so considered as prebiotic agent. Gum Arabic (GA) has anti-inflammatory activity through butyrate. Earlier we proved that regular intake of GA increased fetal hemoglobin and anti-oxidant capacit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The latter was discovered as a physiological modifier for different body functions such as the modulation of cell proliferation, apoptosis, regulation of angiogenesis, and inflammation ( 18 ). The anti-inflammatory effect of Gum Arabic has been investigated in various diseases and conditions ( 19 21 ). As reported earlier, the effect of GA is an anti-inflammatory agent among RA patients, since it decreases the level of TNF α and the disease severity score among RA patients ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter was discovered as a physiological modifier for different body functions such as the modulation of cell proliferation, apoptosis, regulation of angiogenesis, and inflammation ( 18 ). The anti-inflammatory effect of Gum Arabic has been investigated in various diseases and conditions ( 19 21 ). As reported earlier, the effect of GA is an anti-inflammatory agent among RA patients, since it decreases the level of TNF α and the disease severity score among RA patients ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be clarified by the fact that AG fermentation by colonic bacteria increases serum butyrate concentrations which have an anti-inflammatory effect and act as prebiotics. This outcome was as per an ongoing study 42 that recorded the capacity of AG to diminish the level of CRP in patients with sickle cell anaemia due to its anti-inflammatory effect. Kamal et al 43 found that AG was able to decrease the level of ESR and TNF-alpha in a patient with rheumatoid arthritis and modulate the hepatic and renal profile in a patient with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 94%
“…Their research revealed that daily GA consumption led to a noteworthy reduction in key inflammatory indicators, particularly CRP. The authors assert that GA holds promise as a therapeutic agent for mitigating inflammation in individuals afflicted with SCD (Kaddam & Kaddam, 2020). In a separate investigation, the rectal administration of GA in conjunction with basil seeds has demonstrated formidable anti‐inflammatory and antioxidant potential in a rat model of acetic acid‐induced colitis.…”
Section: Gum Acacia On Inflammation and Inflammatory Diseasesmentioning
confidence: 99%
“…Furthermore, GA exhibited a positive influence on GI symptoms, specifically in improving bowel movements and alleviating bloating, thus indicating its potential role in addressing metabolic syndrome (Jarrar et al, 2021). Recent research has revealed that the consumption of 30 g of GA ( Acacia senegal ) per day for a duration of 12 weeks led to a reduction in direct bilirubin, serum alanine transaminase, CRP, and urea levels among patients with chronic sickle cell anemia, while there was no significant impact observed on serum aspartate transaminase levels (Kaddam et al, 2019; Kaddam & Kaddam, 2020).…”
Section: Gum Acacia On Inflammation and Inflammatory Diseasesmentioning
confidence: 99%